2019
DOI: 10.1021/acsami.9b04915
|View full text |Cite
|
Sign up to set email alerts
|

MoS2-Decorated Laser-Induced Graphene for a Highly Sensitive, Hysteresis-free, and Reliable Piezoresistive Strain Sensor

Abstract: Advancement of sensing systems, soft robotics, and point-of-care testing requires the development of highly efficient, scalable, and cost-effective physical sensors with competitive and attractive features such as high sensitivity, reliability, and preferably reversible sensing behaviors. This study reports a highly sensitive and reliable piezoresistive strain sensor fabricated by one-step carbonization of the MoS2-coated polyimide film to obtain MoS2-decorated laser-induced graphene. The resulting three-dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
132
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(134 citation statements)
references
References 63 publications
2
132
0
Order By: Relevance
“…The linear resistance profile with laser parameters such as engraving power, scan line, and raster speed were optimized (see Figure S2, Supporting Information) in our previous report. [ 15 ] To achieve high stretchability, elastic recovery, high cycling stability, and solution processability, we introduced polystyrene‐ block ‐poly(ethylene‐ ran ‐butylene)‐ block ‐polystyrene (SEBS) as a substrate material for BP@LEG composite. As a functional material, poly(allylamine) passivated BP and LEG composite material was used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The linear resistance profile with laser parameters such as engraving power, scan line, and raster speed were optimized (see Figure S2, Supporting Information) in our previous report. [ 15 ] To achieve high stretchability, elastic recovery, high cycling stability, and solution processability, we introduced polystyrene‐ block ‐poly(ethylene‐ ran ‐butylene)‐ block ‐polystyrene (SEBS) as a substrate material for BP@LEG composite. As a functional material, poly(allylamine) passivated BP and LEG composite material was used.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism can be linearized for a longer range by introducing bridging material, as reported in our previous study. [ 15 ] We reported on a piezoresistive strain sensor that exploited MoS 2 as the bridging material in a simple layout that can detect the strain only.…”
Section: Introductionmentioning
confidence: 99%
“…The resistance response was stable and nearly linear under the lower strain loading. Since fewer cracks were grown, and the interspaces between graphene flakes dominated the variation in resistance under a lower strain loading [28]. Therefore, the steady response range of the wavy-LIG sensor was 0-31.8% and the planar-LIG sensor was 0-40.4%.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the excellent mechanical performance and high conductivity, laser-induced graphene (LIG) is the ideal material to prepare a strain sensor [ 25 , 26 , 27 , 28 ]. LIG can be synthesized with a CO infrared laser to scan on the polyimide (PI) film in the air, which is a one-step synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Luo et al found that the laser conditions dictating the morphology and structure of LIG had great effect on piezoelectric sensor's performance, and the optimized LIG sensor showed higher gauge sensitivity than commercial strain gauge by nearly 10 times [75]. Chhetry and co-workers designed a MoS 2 /LIG strain sensor for the detection of voice, eye-blinking, and pulse wave [76]. The decoration of MoS 2 significantly reduced the crack in LIG and improved the mechanical strength of the sensor.…”
Section: Lig-based Mechanic Sensorsmentioning
confidence: 99%